An overview of the developments of the European Common Fisheries Policy regarding sustainable development and its regionalisation in Portugal and the Autonomous Regions - Vieira, Rui Castro (UNIO – EU Law Journal, 2019)
The European integration is not only a continental, but also a maritime integration, with the development of a maritime market including its maritime resources like fisheries. The development of the Common Fisheries Policy, in the European Union, has been marked by a few peculiar principles and tension among Member States. These developments have also been challenged by the developments of International Law, especially the Law of the Seas Convention, as well as the increasing attention given to a sustainable development and the need for maritime environmental development. The latest years have also been marked by a need for decentralization and regionalisation of the Common Fisheries Policy. The Iberian nations, especially Portugal, are a distinctive case with the rather difficult Common Fisheries Policy Integration. In spite of that, its singularity regarding its maritime presence and autonomic decentralized model give new potential for a new management and development of a decentralized Common Fisheries Policy, as well as a new possibility for sustainable development. In this paper, we analyse the development of the European Common Fisheries Policy as well as its role and interaction with International Law and the new concerns regarding sustainability of fishing stocks and its new management approach and needs for regionalisation. We also analyse its repercussions on Portugal and the potential offered by its own maritime and territorial peculiarities with its archipelagos and their own qualities and aptitude for a sustainable integration of the Common Fisheries Policy.